Lopinavir/Ritonavir Treatment Induces Oxidative Stress and Caspaseindependent Apoptosis in Human Glioblastoma U-87 MG Cell Line. - Gratton, Rossella; Tricarico, Paola Maura; Guimarães, Rafael Lima; Celsi, Fulvio; Crovella, Sergio (Curr HIV Res, 2018)
BACKGROUND: Lopinavir and Ritonavir (LPV/r) treatment is widely used to prevent HIV mother-to-child transmission. Nevertheless, studies related to the impact of these compounds on patients, in particular in the foetus and newborns, are strictly required due to the controversial findings reported in the literature concerning possible neurologic side effects following the administration of these drugs. OBJECTIVES: In our study, we evaluated the impact of LPV/r treatment on the human glioblastoma U- 87 MG cell line. METHODS: In order to evaluate the influence of Lopinavir and Ritonavir in terms of oxidative stress (ROS production), mitochondrial morphology and apoptotic cell death, the latter either in the presence or in the absence of caspase-3 and -9 inhibitors, we treated U-87 MG with increasing doses (0.1-1-10-25-50 µM) of Lopinavir and Ritonavir for 24h, either in single formulation or in combination. ROS production was measured by flow cytometry using H2DCFDA dye, mitochondrial morphology was evaluated using MitoRed dye and apoptotic cell death was monitored by flow cytometry using Annexin V-FITC and Propidium Iodide. RESULTS: We observed that co-treatment with Lopinavir and Ritonavir (25 and 50 µM) promoted a significant increase in ROS production, caused mitochondrial network damage and induced apoptosis in a caspase-independent manner. CONCLUSION: Based on our findings, concordant with others reported in the literature, we hypothesize that LPV/r treatment could not be entirely free from side effects, being aware of the need of validation in in vivo models, necessary to confirm our results.